2013
DOI: 10.1002/anie.201209815
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of 1‐(1‐Naphthyl)ethylamine from Solution onto Platinum Surfaces: Implications for the Chiral Modification of Heterogeneous Catalysts

Abstract: Chiral modification of catalysts: A comparative in situ reflection–absorption infrared spectroscopy study of the adsorption of 1‐(1‐naphthyl)ethylamine on Pt surfaces from solution indicated bonding mainly through the amine group and not the aromatic ring as commonly assumed (see picture). In light of these results, a rethinking of the existing model for chiral modification of catalysts may be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Only S-NEA, 1-naphthylmethylamine (NMA), and quinoline adsorb on the platinum surface to any significant extent;n o measurable uptake could be detected with either 1-ethylnaphthalene (EtN) or S-N,N-dimethyl-1-(1-naphthyl)-ethylamine (S-DNE). Unfortunately,i ti sd ifficult to quantify the signals from these IR spectra to calculate surface coverages for the adsorbed species.H owever,i ti se asy to see that, on average,the intensities of the most prominent peaks in the IR traces for S-DNE and EtN are at least one order of magnitude weaker than those for NEA, NMA, and quinoline,avariation not seen in the spectra of the pure compounds.W hat is significant about the results in Figure 2isthat, although all of these compounds contain aromatic rings (naphthalene or quinoline), only the ones with aN H 2 moiety are capable of bonding to the platinum surface.T he common wisdom has been that chiral modifiers adsorb on the metal surface via their aromatic ring, [7][8][9][10][11][12][13][14][15][16] but that does not appear to be the case here.Inprinciple,the species detected by IR could be bonded to the acidic sites of the alumina support, but we have previously shown that the same trend is seen for adsorption on ap latinum foil, where no oxide surfaces are present; [17] only the behavior of quinoline is different between the two cases (quinoline adsorbs on Pt/Al 2 O 3 but not on the platinum foil). Blank experiments were also carried out with the support alone to rule out this possibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only S-NEA, 1-naphthylmethylamine (NMA), and quinoline adsorb on the platinum surface to any significant extent;n o measurable uptake could be detected with either 1-ethylnaphthalene (EtN) or S-N,N-dimethyl-1-(1-naphthyl)-ethylamine (S-DNE). Unfortunately,i ti sd ifficult to quantify the signals from these IR spectra to calculate surface coverages for the adsorbed species.H owever,i ti se asy to see that, on average,the intensities of the most prominent peaks in the IR traces for S-DNE and EtN are at least one order of magnitude weaker than those for NEA, NMA, and quinoline,avariation not seen in the spectra of the pure compounds.W hat is significant about the results in Figure 2isthat, although all of these compounds contain aromatic rings (naphthalene or quinoline), only the ones with aN H 2 moiety are capable of bonding to the platinum surface.T he common wisdom has been that chiral modifiers adsorb on the metal surface via their aromatic ring, [7][8][9][10][11][12][13][14][15][16] but that does not appear to be the case here.Inprinciple,the species detected by IR could be bonded to the acidic sites of the alumina support, but we have previously shown that the same trend is seen for adsorption on ap latinum foil, where no oxide surfaces are present; [17] only the behavior of quinoline is different between the two cases (quinoline adsorbs on Pt/Al 2 O 3 but not on the platinum foil). Blank experiments were also carried out with the support alone to rule out this possibility.…”
mentioning
confidence: 99%
“…Figure 2a lso shows that the spectra of the adsorbed species are quite different to those of the pure compounds. These differences are explored in more detail for the case of S-NEA in Figure 3, which displays IR absorption spectra for (from bottom to top): 1) pure NEA (acquired in transmission mode);2 ,3) NEA adsorbed on aPt(111) single crystal under ultra-high vacuum (UHV; acquired in single reflectionabsorption, or RAIRS,m ode) after two different exposures, namely,1 .5 L( which leads to ac overage close to monolayer saturation;1L= 1 10 À6 torr s), and 0.5 L( representative of the low-coverage limit); [18] 4) NEA adsorbed from a1m m CCl 4 solution onto apolished platinum foil [17,19] (also acquired in RAIRS mode but using adifferent setup); [20] and 5,6) NEA adsorbed from 1mm CCl 4 solutions,o n1wt %P t/Al 2 O 3 and 1wt%Pt/SiO 2 commercial catalysts,respectively (acquired in ATR-IR mode). [21] An assignment of the peaks,b ased on previous studies, [18] is provided in Table 1.…”
mentioning
confidence: 99%
“…The activation energies calculated confirm that that self-assembly of glycine on low-index copper surfaces is indeed an activated process, which is facile in the temperature range (typically from 300 K to 420 K) generally employed in experiments. We suggest that the walking mechanism predicted in this study might play a key role in the formation of similar self-assembled systems relevant for nanotechnology and surface chemistry, such as thiolates 38 , amines 39 or chiral organic acids 40 on metal surfaces.…”
Section: Discussionmentioning
confidence: 68%
“…The common wisdom has been that chiral modifiers adsorb on the metal surface via their aromatic ring, but that does not appear to be the case here. In principle, the species detected by IR could be bonded to the acidic sites of the alumina support, but we have previously shown that the same trend is seen for adsorption on a platinum foil, where no oxide surfaces are present; only the behavior of quinoline is different between the two cases (quinoline adsorbs on Pt/Al 2 O 3 but not on the platinum foil). Blank experiments were also carried out with the support alone to rule out this possibility.…”
Section: Figurementioning
confidence: 73%
“…Figure also shows that the spectra of the adsorbed species are quite different to those of the pure compounds. These differences are explored in more detail for the case of S ‐NEA in Figure , which displays IR absorption spectra for (from bottom to top): 1) pure NEA (acquired in transmission mode); 2,3) NEA adsorbed on a Pt(111) single crystal under ultra‐high vacuum (UHV; acquired in single reflection–absorption, or RAIRS, mode) after two different exposures, namely, 1.5 L (which leads to a coverage close to monolayer saturation; 1 L=1×10 −6 torr s), and 0.5 L (representative of the low‐coverage limit); 4) NEA adsorbed from a 1 m m CCl 4 solution onto a polished platinum foil (also acquired in RAIRS mode but using a different setup); and 5,6) NEA adsorbed from 1 m m CCl 4 solutions, on 1 wt % Pt/Al 2 O 3 and 1 wt % Pt/SiO 2 commercial catalysts, respectively (acquired in ATR‐IR mode) . An assignment of the peaks, based on previous studies, is provided in Table .…”
Section: Figurementioning
confidence: 99%